ANALISIS YURIDIS TERHADAP PELAKSANAAN PEMBAGIAN HARTA WARISAN YANG DIKUASAI OLEH SALAH SATU AHLI WARIS (Studi Kasus Putusan Mahkamah Agung No 2134 K/PDT/1989) - ENDAH MAYANA (PREMISE LAW JURNAL, 2015)
Islamic Inheritance Law basically applies to all of the Muslims in the world. The problem can occur if the inherited property is not directly divided. One of the cases is what is seen in the Decision of Supreme Court No: 2134 K/PDT/1989. The chronology of this case begins with the polygamy done by H. Muhammad Jamil Daring his marriage with his first wife, ff. Muhammad Jamil did not have any property, then daring his marriage with his second wife, H. Muhammad Jamil had a lot of property. The problem occurred after H. Muhammad Jamil, the father of the plaintiff, died. Several problems discussed in this analytical descriptive study with normative juridical approach were the factors causing a part of the heirs controlled the inherited property, the legal action taken by the heirs whose rights were held by the other heirs, and how the analysis of the Supreme Court was done in settling the case. The factors causing the heir hold the inherited property were that the heir thought that the property was those earned by his father during his marriage with his mother who was the second wife of the testator that the heir thought that he was more entitled to the property left by their father compared to his other brothers and sisters, Legal action taken by the heirs whose rights was held by the another heir was to conduct deliberation, since (his deliberation did not work, the heirs whose rights was held by the another heir eventually filed the application for decision to Tebing Tinggi. Keywords: Juridical Analysis, Inherit Property Distribution, Being Held